A MODEL FOR DEVELOPING LINGUISTIC CULTURAL AND COMMUNICATIVE COMPETENCE OF FUTURE TRANSLATORS (Scientific journal of the Fergana State University, 2024)
This article analyzes and develops a model for the development of linguistic, cultural and communicative competence of future translators, the stages of its organization and the possibilities of its implementation.